Pengaruh Pertumbuhan Ekonomi, Upah Minimum, Dan Pengangguran Terhadap Kemiskinan Di Kabupaten Lamongan - Siti Hanifah; Nurul Hanifa (Jurnal Ekonomika : INDEPENDEN, 2021)
This study aims to determine the effect of economic growth, minimum wage, and unemployment on poverty levels. The data used at the time of this research is secondary data obtained from the relevant agencies, namely BPS in Lamongan Regency with a quarterly period from 2010 to 2020. The data analysis method used for this research is multiple linear regression model with the help of software eviews 10. The results of the study show that the variables of economic growth, minimum wage, and unemployment have a significant positive effect on poverty. In partial terms, the variables of economic growth, and the minimum wage have a significant negative effect on poverty. But the unemployment variable has a negative and insignificant effect on poverty.